A brief report and analysis on the July 19, 2019, explosion in the Yima gasification plant in Sanmenxia, China. Issue 1 (21st August 2019) - Wang, Bing; Zhu, Zhaozhen
Abstract: This short article presents some basic facts related to the explosion accident that occurred on July 19, 2019, in the Yima gasification plant located in Sanmenxia City, Henan Province, China. This huge explosion killed 15 people and seriously injured 16. The article introduces the background, scenes, and possible causes of this explosion. Moreover, this study proposes some measures to prevent and control similar accidents. This article can provide some basic information for a further investigation and analysis on this explosion.